Validation of the non-verbal immediacy scale (NVIE) to evaluate teacher behavior styles - Asencios Trujillo, Lucía (2024)
Nonverbal communication as a social skill influences student motivation; therefore, during the pedagogical process, teaching staff must possess interpersonal skill to emit assertive behavior; in order to have a measurement scale on non-verbal behavioral styles. They items were organized into three dimensions: assertive, aggressive and passive. The objective was to analyze the psychometric properties of the Non-Verbal Immediacy Scale (NVIE) in teachers. Their study approach was quantitative, with a non-experimental factorial design. The sample of 150 subjects was obtained through non-probabilistic sampling of a population of 373.The programs used were SPSS.23 and Lisrel. The results showed a pearsoʹn correlation coefficient greater than .30 between the items of its dimensions, presenting a homogeneous measurement between them. The Cronbachʹs Alpha indices of the scales range from .60 to .82, which shows good internal consistency. The exploratory analysis (EFA) gave an approximation to the model with a solution for three factors representing 67.54% of its variance. Through confirmatory analysis (CFA), the similarities of the sample covariation matrices with the matrix of the alternative model on the same data were determined, obtaining satisfactory adjustments for the parameters (X2-RMSEA-RMR-GFI-AGFI), corroborating the proposed hypothesis. It is concluded that with the graphic representation of the alternative-recursive-NVIE model, the cause-effect relationship of the three dimensions is visualized, with their indicators, establishing in a valid and reliable manner its use as a measurement scale in studies of behavioral styles non verbal.